To Compare Isobaric 0.5% Levobupivacaine With Isobaric 0.5% Ropivacaine In Brachial Plexus Block For Elective Upper Limb Surgery - Sharma, Utsav; Thakur, Kunwar Singh; Goyal, Preeti; Choudhary, Bhanu (Academia Anesthesiologica International, 2020)
Background: The purpose of the investigation is to Compare Isobaric 0.5% Levobupivacaine With Isobaric 0.5% Ropivacaine In Brachial Plexus Block For Elective Upper Limb Surgery. Subjects and Methods: Intravenous access was obtained in the limb opposite to that undergoing surgery with an intravenous cannula-18G. Standard monitors, ECG, pulse oximeter, non invasive blood pressure, respiratory monitoring were connected and monitored continuously in all the patients and recorded at interval of 0, 5, 10, 15, 20, 30, 60 minutes in the first hour and every 30 minutes thereafter till the end of surgery. All emergency equipments including intubation aids and drugs such as midazolam, thiopentone or propofol and 20% of lipid emulsion were kept ready to deal with any adverse events during the course of procedure/ surgery. Sixty patients aged between 18yrs and 60yrs physical status ASA grade 1 and ASA grade 2 undergoing elective upper limb surgeries were included in the study. Results: Demographic details Age, sex and weight were comparable in both the groups (no significant statistical difference was observed). These eliminated possible bias in term of gender, age, and weight distribution which can alter the study drugs pharmacokinetics and dynamics. The average pulse rate, mean arterial pressure, oxygen saturation and respiratory rate readings at frequent intervals did not differ significantly between two intervention groups ( p> 0.05 for all) No clinically significant bradycardia or hypotension was noted. Conclusion: Levobupivacaine should be considered for peripheral nerve block when postoperative analgesia is a concern but not when an early return of motor function is desired in postoperative period for upper limb elective surgeries. Demographic details Age, sex and weight were comparable in both the groups (no significant statistical difference was observed). These eliminated possible bias in terms of gender, age, and weight distribution which can alter the study drug pharmacokinetics and dynamics. The average pulse rate, mean arterial pressure, oxygen saturation and respiratory rate readings at frequent intervals did not differ significantly between two intervention groups ( p> 0.05 for all) No clinically significant bradycardia or hypotension was noted.